Pengelolaan anggaran daerah di RSU Mayjen H.A. Thalib Kabupaten Kerinci Propinsi Jambi - AFRIDA, Irma ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Background: The development of hospital was influenced by economy factor. Therefore, a hospital need to be managed professionally and should have careful exploration especially in financial with independent, accountable and transparant of financial management in order to support operational activity which at the end could be focused on the improvement of service quality in hospital toward community and able to improve competitiveness in planning and control of human resources with budget management. General Hospital of Mayjen H.A. Thalib, district of Kerinci is a hospital with self funding try out unit status since the year of 2003 and yet it still could be functioned by following the procedure of budget liquidation. Objective: This research was aimed to obtained description on the management of regional budget, obstacle and effort being done. Method: This research was a case study design that was located in general hospital of Mayjen H.A. Thalib district of Kerinci. The data was find out through document observation and indepth interview as well as check list that was related with management of regional budget. Result: The process of regional budget management in general hospital of Mayjen H.A. Thalib district of Kerinci has followed the existing regulation. The performance of regional budget management in RSU Mayjen H.A. Thalib district of Kerinci was influenced by budgeting bureacracy that was consisted of process and time of regional budget that was arranged and stated in order to create a budget document as well as capacity of regional budget management that was consisted of human resources and the availability of technology and information. In the management of regional budgeting in hospital, there were some obstacles found that could be well overcomed by hospital in order to make the operational activity could running well. Conclusion and suggestion: Regional budgeting management in RSU Mayjen H.A. Thalib district of Kerinci was influenced by external and internal factors. The changes of hospital form into self funding unit or general service was expected could give an independency for hospital in managing regional budget.